Enlarging the Purcell Enhancement by Inserting a Dielectric Film in Dielectric‐Loaded Surface‐Plasmon‐Polariton Waveguides. Issue 9 (30th July 2020) - Zhang, Guorui; Liu, Hui; Jia, Shangtong; Li, Hongyun; Li, Zhi; Gong, Qihuang; Chen, Jianjun
Abstract: The deterministic integration of single‐photon emitters with large Purcell enhancements and waveguides is vital for integrated quantum circuits and quantum chips. Purcell enhancements are not only related to waveguide structures, but are also greatly affected by the position of single‐photon emitters in waveguides. Here, the insertion of a thin dielectric film with a controllable thickness between a dielectric strip and a metal surface to precisely position a single‐photon emitter in a dielectric‐load surface‐plasmon‐polariton (DLSPP) waveguide is proposed, and the Purcell enhancement is greatly enlarged. Simulations show that the vertical position of the single‐photon emitter above the metal surface is more important than its in‐plane position in the DLSPP waveguide for achieving enlarged Purcell enhancements. In the experiment, the vertical position of the single‐photon emitter in the modified DLSPP waveguide is controlled by evaporating a thin MgF2 film, and the in‐plane position is controlled by combining aligned electron beam lithography and photoluminescence imaging. The Purcell factor in the emitter‐waveguide system is measured to be F p = 22.4, which is greater than those obtained using conventional DLSPP waveguides ( F p ≤ 6.0) in previous studies. Abstract : A thin dielectric film with a controllable thickness is proposed to be inserted between a dielectric strip and a metal surface to precisely position a single‐photon emitter in a dielectric‐load surface‐plasmon‐polariton (DLSPP) waveguide. The Purcell enhancement is greatly enlarged, and the important problem of deterministic integration of a single‐photon emitter into a DLSPP waveguide is addressed.